Physiological correlates of cycling performance in amateur mountain bikers - Vaitkevièiute, D.; Milašius, K. (Education. Physical training. Sport, 2012)
Research background and hypothesis. Aerobic fitness of high-performance mountain bikers explains about 40% of variance in performance. This suggests that other factors such as anaerobic power and capacity as well as technical abilities need to be considered in the physiological assessment (Impellizzeri et al., 2005 a). We found a lot studies investigating track and road cyclists, but there are no studies concerning the relationship between physiological tests and cycling performance in Lithuanian mountain bikers. The aim of this study was to investigate the physiological correlates of cycling performance in amateur mountain bikers. Research methods. Fifteen Lithuanian mountain bikers participated in the study. The 10-second test was performed to estimate special alactic anaerobic power output, whereas ae 30-second Wingate test was performed to estimate composite alactic anaerobic glycolytic power output. For the evaluation of the aerobic capacity, a progressive incremental laboratory cycling test to exhaustion was performed. Research results. We found a significant negative correlation between cycling performance and alactic anaerobic relative peak power output (r = -0.534, p < 0.05) and lactate concentration after the progressive incremental cycling test to exhaustion (r = -0.625, p < 0.05). However, we did not find a significant correlation between cycling performance and VO2max (r = -0.024, p > 0.05) and composite alactic anaerobic glycolytic power output (r = -0.269, p > 0.05). Discussion and conclusions. Our findings suggest that alactic anaerobic power output and active glycolysis play a very important role in off-road cycling performance. This is essential because of the fast starting phase of the race and steep climbs.